Pemenuhan Nafkah Anak Sebagai Implementasi Keadilan dalam Hukum Keluarga: Model Keadilan Berkelanjutan Pascaperceraian - M. Aziz Indrayanto (Kartika: Jurnal Studi Keislaman, 2026)
The fulfillment of child support after divorce constitutes a parental responsibility that does not cease to exist, yet its implementation often encounters obstacles, ranging from the determination of a fair amount, compatibility with economic capacity, to the effectiveness of court decisions. This normative legal research analyzes the implementation of justice in child support fulfillment and formulates a sustainable justice model. Employing statutory, conceptual, and case approaches, primary legal materials include legislation, the Compilation of Islamic Law, Supreme Court Circular Letters No. 3 of 2018 and No. 5 of 2021, and court decisions, supported by secondary materials from relevant literature. The findings affirm that child support is an inherent right, and justice must be achieved through a balance between the child's actual needs, the parent's economic capacity, the best interests of the child, and the sustainability of obligation enforcement. Supreme Court Circular Letter No. 3 of 2018 guides judges to explore economic capacity and basic needs, while Circular Letter No. 5 of 2021 strengthens guarantees through the possibility of asset seizure. This research offers a four-stage sustainable justice model: justice in determination, guarantee, implementation, and adjustment, which places legal success not merely on the existence of a support order, but on the fulfillment of children's rights in a real, proper, and continuous manner.